Vanillin as a cardioprotective agent against anthracycline-induced cardiotoxicity in Wistar rats via modulation of oxidative stress and molecular docking analysis - N. G. Dighe; S. B. Dighe; S. B. Bhawar; R. D. Ghogare; V. A. Patole (Journal of Applied Pharmaceutical Research, 2026)
Background: Doxorubicin (DOX) is limited by dose-dependent cardiotoxicity mediated by reactive oxygen species (ROS) and oxidative stress. Natural phenolic compounds, such as vanillin, with antioxidant properties, are being explored as cardioprotective agents. This study evaluated vanillin using integrated in silico and in vivo approaches. Methodology: Molecular docking assessed vanillin–cardiac protein interactions, and ADMET profiling evaluated drug-likeness. In vivo, DOX-induced cardiomyopathy was established in male Wistar rats (n=6) via cumulative intraperitoneal dosing (16 mg/kg). Vanillin (50, 100, and 200 mg/kg) was administered orally 30 minutes post-DOX for 28 days. ECG parameters, cardiac biomarkers (CK-MB, AST, LDH, cTn-I), oxidative stress markers (MDA, SOD, GSH, catalase), and histopathology were analyzed. Results & Discussion: In silico analysis revealed that vanillin binds to the CK-MB active site, demonstrating a docking interaction comparable to that of doxorubicin. In vivo, Doxorubicin treatment caused significant cardiac dysfunction, characterized by QTc prolongation and ST-segment depression. Serum biomarkers of myocardial injury (CK-MB, Troponin-I, LDH, AST) were significantly elevated, while myocardial antioxidant levels (SOD, GSH, CAT) were depleted in the DOX group. Vanillin co-administration (200 mg/kg) significantly attenuated these alterations, restoring QTc intervals and reducing oxidative stress markers. Histopathological scoring confirmed improving myocardial architecture from severe damage in the DOX group to near-normal morphology in the high-dose Vanillin group. Conclusion: Vanillin exerts cardioprotective effects via antioxidant mechanisms, stabilization of cardiac biomarkers, and maintenance of myocardial integrity, indicating its promise as an adjunct strategy against anthracycline-induced cardiotoxicity.